2018
DOI: 10.14742/ajet.3575
|View full text |Cite
|
Sign up to set email alerts
|

Exploring intentional use of a technological proxy, Turnitin, to enhance student academic literacy practices

Abstract: Current pedagogical practices have seen the rapid spread of technological tools that carry out tasks on behalf of the learner; we use the term technological proxy to refer to these tools. A popular technological proxy used by students worldwide is a text-matching software called Turnitin. Turnitin alerts users to sections of an assignment that appear to match materials that exist in some other published or previously submitted form. This paper reports on a small case study that examined how university students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Previous studies have indicated that higher academic motivation may enhance the use of digital media for learning (Chang et al, 2019). Achievement goal orientations could also be related to how students utilize learning possibilities provided by digital media and tools (Orlando et al, 2018). For example, mastery-oriented students might be more engaged in learning new skills and gaining knowledge with the help of digital tools; performanceoriented students, in contrast, might merely aim to complete the task at hand (Orlando et al, 2018).…”
Section: Orientationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that higher academic motivation may enhance the use of digital media for learning (Chang et al, 2019). Achievement goal orientations could also be related to how students utilize learning possibilities provided by digital media and tools (Orlando et al, 2018). For example, mastery-oriented students might be more engaged in learning new skills and gaining knowledge with the help of digital tools; performanceoriented students, in contrast, might merely aim to complete the task at hand (Orlando et al, 2018).…”
Section: Orientationsmentioning
confidence: 99%
“…Achievement goal orientations could also be related to how students utilize learning possibilities provided by digital media and tools (Orlando et al, 2018). For example, mastery-oriented students might be more engaged in learning new skills and gaining knowledge with the help of digital tools; performanceoriented students, in contrast, might merely aim to complete the task at hand (Orlando et al, 2018). Digital tools can also support students' need for autonomy and competence (i.e., connected learning; Barron, 2006;Ito et al, 2013;Kumpulainen & Sefton-Green, 2014), which becomes increasingly important during adolescence (Eccles et al, 1993).…”
Section: Orientationsmentioning
confidence: 99%
“…Another factor we considered was the sample size of the population under study. We noted that some studies that focused on using text-matching software as an educational intervention included author-identified limitations that included a small sample size [42,54,64,75,102,119,142]. e nature of the studies involving teaching and learning interventions varied in their scope and approach, and we found no evidence of educational intervention studies that had replicated previous studies, further limiting our ability to definitively determine the effectiveness of TMS as an educational intervention.…”
Section: Resultsmentioning
confidence: 90%
“…With applications such as Turnitin TM , plagiarism is narrowly conceived as something that can detected through patterns of text matching. It is argued that such software can be used as a pedagogical tool to improve students' writing (Halgamuge, 2017;Orlando et al, 2018); however, in such a context scholarly writing is rendered an exercise in paraphrasing to beat the machine. Citation and paraphrasing become a fig leaf covering the naked cobbling together of sources in aid of providing a passable imitation of academic writing.…”
Section: Rachel Buchanan University Of Newcastle Australiamentioning
confidence: 99%